2020
DOI: 10.1016/j.ijso.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing falls risk and associated factors among urban community dwellers older adults in Gondar town, Northwest Ethiopia 2019: A cross sectional study

Abstract: Background: Falls are the major public health problems among older adults of age 65 years and older. The risk of falling in the elderly is a combined result of multiple factors that can be from intrinsic or extrinsic in its origin. In Ethiopia, there is no study done to assess the falls risk status among older adults. Objective: The objective of this study was to assess the magnitude of falls risk and its associated factors in urban community dwellers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The United Nations population division estimated that the population aged 65 years and above accounted for 3.5% of Ethiopia's total population in 2019 [24], and this proportion is expected to increase to 3.8% by 2050. Already several studies conducted on the older population in Ethiopia reported a higher occurrence of falls [25,26], depression [27], hypertension [28], higher eye care service utilization [29], patterns of extensive psychotic medications use [30], polypharmacy, and PIM use [31][32][33][34][35][36][37][38]. On the other hand, deprescribing strategies [23] and emphasis on the importance of medication safety and medication-related quality of life have also been described [39].…”
Section: Introductionmentioning
confidence: 99%
“…The United Nations population division estimated that the population aged 65 years and above accounted for 3.5% of Ethiopia's total population in 2019 [24], and this proportion is expected to increase to 3.8% by 2050. Already several studies conducted on the older population in Ethiopia reported a higher occurrence of falls [25,26], depression [27], hypertension [28], higher eye care service utilization [29], patterns of extensive psychotic medications use [30], polypharmacy, and PIM use [31][32][33][34][35][36][37][38]. On the other hand, deprescribing strategies [23] and emphasis on the importance of medication safety and medication-related quality of life have also been described [39].…”
Section: Introductionmentioning
confidence: 99%
“…Four regional states (counties) of Ethiopia were represented in the studies. Four studies were conducted in the Amhara region [ 23 , 33 , 51 , 52 ], three studies conducted in Addis Ababa [ 31 , 36 , 53 ], two studies were conducted in Oromia [ 1 , 24 ] and two studies were conducted in Harar [ 50 , 54 ]. Three studies [ 31 , 53 , 54 ] did not report the mean age of their study participants, whereas the mean age of the participants in the other included studies ranged from 66.69 to 75.46 years.…”
Section: Resultsmentioning
confidence: 99%
“…Because the prevalence of cognitive impairment increases with age, the differential diagnosis of depression and dementia becomes increasingly difficult with age. Our review identified only two studies [ 50 , 52 ] that assessed cognitive impairment among older people. The underlying neuropathological conditions that lead to mild cognitive impairment (MCI) or dementia may also contribute to depression; thus later-life depression, MCI, and dementia may fall in a clinical continuum [ 81 ].…”
Section: Discussionmentioning
confidence: 99%